An Extracellular Pectinase from ISH16 Bacteria Isolated Induced by Coffee Pulp Waste Substrate - Kahar Muzakhar; Farah Salma Elida; Ramdhan Putrasetya; Siswoyo Siswoyo; Rudju Winarsa; Hidayat Teguh Wiyono (UIN Sunan Gunung Djati Bandung, 2022)
An α-1,4-glycosidic bonds galactoses pectin, mainly composed of a D-galacturonic acid chain, are important biomaterial widely used in industries. Utilizing this material, a bioprocess, including the biocatalysis pectinase, is often needed. Pectinase production was optimized in 7 days SSF at 37°C, and the pectinase activities were daily measured by the method of Somogy-Nelson. The optimum pectinase production was 0.166 U/ml on the fourth day SSF. Purification using open column ion exchange chromatography DEAE cellulose DE-52 resulted in 1030.9 folds of pectinase purity with a yield of 25.9%. The enzyme was at optimal activity at pH six and attended stable in the pH range of 5.5-8, while optimal activity at a temperature of 50°C and was stable in the range of 30-45°C. The pectinase activity increased by 120% with the addition of 10 mM Mg2+, and 95% retained when 10 mM Ca2+ was added. The presence of 10 mM Na+, K+, and Fe2+ resulted in a slight effect of activity at 85%, 83%, and 78%. However, it was strongly inhibited by 10 mM Al3+ and retained 25%. Based on the results above, the microbial utilization of coffee pulp waste by ISH16 bacteria pectinolytic is one opportunity to produce valuable pectinase with low-cost production, so comprehensive examination in large-scale production is needed too. In this paper, all research detail steps were described.